Exploring the Social and Environmental Significance of the "Kang Pisman" Waste Management Movement in Bandung, Indonesia - Bintarsih Sekarningrum; Aisha Putri Utami; Desi Yunita (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2024)
"Kang PisMan" is a waste management movement in Bandung City focused on reducing, segregating, and exploiting refuse. Therefore, this study aimed to analyze the meaning of the movement in waste management and the broader impact of similar initiatives across the city of Bandung. Adopting Herbert Blumer's Symbolic Interactionism theory, the study analyzed the society's interpretation of the "Kang PisMan" movement, through the exploration of diverse experiences and perceptions of the community, the underlying actions and subsequent responses originating from this definition were further investigated. The results showed that the community participation in the "Kang PisMan" movement was influenced by the meaning as an initiative addressing waste management, providing benefits, and emphasizing collective responsibility. The implications of this meaning on waste management movements lay in fostering community contribution based on awareness, thereby enabling the initiative to implement sustainability.